2014
DOI: 10.1111/maps.12281
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid composition of the Sutter's Mill CM2 carbonaceous chondrite

Abstract: Abstract-We determined the abundances and enantiomeric compositions of amino acids in Sutter's Mill fragment #2 (designated SM2) recovered prior to heavy rains that fell April 25-26, 2012, and two other meteorite fragments, SM12 and SM51, that were recovered postrain. We also determined the abundance, enantiomeric, and isotopic compositions of amino acids in soil from the recovery site of fragment SM51. The three meteorite stones experienced terrestrial amino acid contamination, as evidenced by the low D/L rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 67 publications
6
49
0
Order By: Relevance
“…Also, the amino acid analysis (Burton et al. ) suggests a higher contamination for SM12 than for SM2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the amino acid analysis (Burton et al. ) suggests a higher contamination for SM12 than for SM2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of amino acids (Burton et al. ), which are present in the meteorite at only very low level, showed that SM2 and SM12 may contain amino acids of terrestrial origin, but the extent of the contamination is ambiguous.…”
Section: Samples and Experimental Detailsmentioning
confidence: 99%
“…The β‐alanine to glycine ratio of Diepenveen at 1.95 is closer to that typical of CI chondrites (~2–3) than to CM chondrites (~0.5) (Burton et al. ) and indicates that the fragment analyzed experienced significant parent body alteration under mildly warmer temperatures than typical for CM chondrites. In comparison, the least known aqueously altered, and only weakly affected by thermal metamorphism CM chondrite Paris, had a ratio of 0.15 (Martins et al.…”
Section: Discussionmentioning
confidence: 62%
“…For comparison, in a terrestrial soil sample the ratio of glycine: β‐alanine: γ‐amino‐ n ‐butyric acid were measured to be 1:0.2:0.1, whereas in Diepenveen the ratio of these amino acids is 1:1.3:2.2 (Burton et al. ). The significantly higher relative abundances of β‐alanine and γ‐amino‐ n ‐butyric acid over glycine (even assuming all of the glycine is indigenous), suggest that the β‐alanine and γ‐amino‐ n ‐butyric acid in this meteorite are predominantly indigenous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation